MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI PERMAINAN KARTU BERGAMBAR PADA ANAK USIA 4-5 TAHUN DI PAUD PERMATA HATI KOTO BARU KUANTAN SINGINGI - Meirita Astuti; Mahdum '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observations in the field of the concept symbol of number is still low and teachers are still using learning methods that dominate and not bervaritif so that learning needs to be given in the form of an illustrated card game. This research aims to know the improved of the symbol concept of number throught the number illustated cards game for children aged 4-5 years old in Permata Hati Kotobaru Kuantan Singingi. Sample used in this study 10 children. As for the data collection techniques are used namely observation. Data analysis techniques using qualitative and quantitative deskritif deskritif. The hypothesis of the research is there influence on signipikan against children after applying arithmetic game picture cards through 2 cycles. After improving by 2 cycles, there is improvement in 91%.